Exploring Communication Patterns Among Adolescents Engaged in Self-Harm: A Social Penetration Approach in Pekanbaru City - Stevens, Gelinas; Zerikho, Chiko (Institute for Law and Economics Studies, 2022)
This research delves into the complex interplay between communication patterns and self-harm among adolescents in Pekanbaru City, employing a Social Penetration Approach as its theoretical framework. The study unfolds layers of insight by exploring how adolescents navigate the challenges of self-harm through communication, both online and offline, within the unique socio-cultural context of Pekanbaru City. A mixed-methods approach, encompassing in-depth interviews and surveys, was employed to capture the diverse facets of communication dynamics. Participants included adolescents engaging in self-harm, providing a rich tapestry of narratives that elucidate the role of communication in their experiences. The research reveals that communication serves as a multifaceted coping mechanism, offering both solace and challenges. Trust within offline relationships is identified as a catalyst for open communication, highlighting the pivotal role of familial and peer dynamics. Importantly, the severity of self-harm behaviors correlates with the preference for online communication, emphasizing the nuanced interplay between the digital realm and mental health. Drawing from the findings, recommendations are proposed for practitioners, policymakers, and educators. Culturally tailored mental health interventions, digital literacy programs, and the integration of mental health education in schools are advocated. Strengthening family support structures and peer-led initiatives within educational settings emerge as crucial strategies, while collaborative community-based approaches are underscored for a holistic impact. In conclusion, this research contributes a nuanced understanding of communication patterns among adolescents engaged in self-harm in Pekanbaru City. The implications for intervention and the identified avenues for future research set the stage for a holistic approach, emphasizing resilience, cultural sensitivity, and community collaboration in addressing the challenges faced by adolescents navigating self-harm in this unique socio-cultural milieu